Simple Eco-Labels to Nudge Customers Toward the Most Environmentally Friendly Warm Dishes: An Empirical Study in a Cafeteria Setting - Slapø, Helena Berz; Karevold, Knut Ivar (Frontiers in Sustainable Food Systems, 2019)
Abstract Background: Food production and consumption contributes to one third of households’ environmental impact. The environmental impact of different food categories varies and in general environmental footprint of meat is high than fish and vegetable options. Environmental food labels have been suggested as a means to sway consumption patterns. The purpose of this study is to test if different simple eco-labels in combination with posters can influence consumers to select environmentally friendly food options. Method: Three different labeling systems were tested on warm dishes in a University cafeteria in Oslo, Norway. The first system was traffic-light labels with three symbols (red, yellow and green), the second system was a single-green label that only labelled the environmentally friendliest dishes, and the third system was a single-red label that only labelled the least environmentally friendly option. Posters were placed in the cafeteria, explaining the labeling systems and the climate impact of different food categories. Outcome measures was sales share of meat, fish and vegetarian dishes. The intervention period was separated in two; the first 20 days (period 1) and 22 last days (period 2) to evaluate if the effects of the labels was different when first introduced and after some months. Results: The traffic-light labels significantly reduced sales of meat dishes with 9% in the period 1 (p < 0.1) but not in period 2. Sales share of fish or vegetarian dishes were not impacted. Single-green and single-red labeling had no effect on sales share of meat, fish or vegetarian dishes. Posters were present during all interventions. Conclusion: Findings suggests that traffic-light labels in combination with posters can improve the eco-friendliness of customers food choices in a cafeteria setting, at least short-term. Future studies should investigate the long-term effects of simple eco-labels. Additionally, one should study the combined effect of symbols with other changes in the choice architecture. Key words: Food choices, behavioral economics interventions, nudging, eco-labels, simple-labels, environmental impact